2021
DOI: 10.1093/mnras/stab2192
|View full text |Cite
|
Sign up to set email alerts
|

A HARPS-N mass for the elusive Kepler-37d: a case study in disentangling stellar activity and planetary signals

Abstract: To date, only 18 exoplanets with radial velocity (RV) semi-amplitude <2 m s−1 have had their masses directly constrained. The biggest obstacle to RV detection of such exoplanets is variability intrinsic to stars themselves, e.g. nuisance signals arising from surface magnetic activity such as rotating spots and plages, which can drown out or even mimic planetary RV signals. We use Kepler-37 – known to host three transiting planets, one of which, Kepler-37d, should be on the cusp of RV detectability with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 113 publications
0
9
0
Order By: Relevance
“…The largest deviation from the fit is observed for Kepler-37 d. Kepler-37 is orbited by three 3 transiting small planets. Kepler-37 d is the largest planet of the system, the mass of which was very recently determined by Rajpaul et al (2021) using radial velocity (RV) observations. The authors obtained a RV based mass of 5.4±1.4 M ⊕ and a dynamical mass of ∼ 4 M ⊕ .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest deviation from the fit is observed for Kepler-37 d. Kepler-37 is orbited by three 3 transiting small planets. Kepler-37 d is the largest planet of the system, the mass of which was very recently determined by Rajpaul et al (2021) using radial velocity (RV) observations. The authors obtained a RV based mass of 5.4±1.4 M ⊕ and a dynamical mass of ∼ 4 M ⊕ .…”
Section: Resultsmentioning
confidence: 99%
“…The authors obtained a RV based mass of 5.4±1.4 M ⊕ and a dynamical mass of ∼ 4 M ⊕ . From the low density of the planet, Rajpaul et al (2021) concluded that either Kepler-37 d is a water-world (> 25% H 2 O) or has a gaseous envelope 4 . In either case, the planet is most probably not a rocky planet consisting of only metallic core and silicate mantle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, some specific observation strategies are commonly used to reduce the contribution of short-timescale activity components (Hatzes et al 2011;Dumusque et al 2011). Second, to correct for variability that evolves at the stellar rotation period (spots and plages), the most basic technique consists of fitting a model to the RV dataset (e.g., sinusoidal functions at the stellar rotation period (Boisse et al 2011), or quasi-periodic Gaussian processes (see, e.g., Aigrain et al 2012;Baluev 2011;Baluev 2013b;Rajpaul et al 2015;Jones et al 2022;Rajpaul et al 2021)). To constrain the parameters of these models, activity indicators (e.g., the S-index (Wilson 1968), logR HK (Noyes et al 1984), or the bisector span (Queloz et al 2001)) are commonly used if correlations with the RV dataset are found.…”
Section: Introductionmentioning
confidence: 99%
“…While some periodogram peaks genuinely describe planets, others are spurious detections resulting from stellar rotation or activity (e.g. Saar & Donahue 1997;Hatzes 2002;Desort et al 2007;Boisse et al 2011;Newton et al 2016;Suárez Mascareño et al 2017;Rajpaul et al 2021). Now that extreme precision spectrographs are on the hunt for terrestrial planets (Jurgenson et al 2016;González Hernández et al 2018;Gupta et al 2021), the need for high-performance activity diagnostics is urgent: while an earthlike planet orbiting a sunlike star yields an RV oscillation with semiamplitude K < 10 cm s −1 , that same star's expected rotational RV modulation has amplitude > 1 m s −1 (Vanderburg et al 2016).…”
Section: Introductionmentioning
confidence: 99%